Parents' influence on children's online usage - Yusuf, Sarina; Osman, Mohd Nizam; Hassan, Md. Salleh; Teimoury, Misha (Elsevier, 2014)
Children nowadays has unlimited access to the Internet that possibly will harm them, thus parents’ roles in mitigating their children online risks is crucial. Previous studies show a positive parent-child attachment may reduce the risks. A survey was conducted and a total of 387 participants aged 9 to 16 have been recruited to completed a 14-item questionnaire form. The instrument consists of three sub-scales, namely trust, communication and alienation. Results showed that almost 80% of children in this study trust their parents, feel their parents’ concern (75%), and depend on their parents (74%). Malaysian children are actually very in need to be safe during online due the facts that they knew regarding the Internet effects. They also show a willingness to do the right things by letting their parents involve into their online live activities.